Gender Differences In Perceived School Support, Self-Esteem, Academic Fatigue, And Engagement Among Nigerian Undergraduates - Pillay, Jace; Olatunbosun, Stella Oluwakemi (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Various studies have found differences in perceived social support, self-esteem, academic fatigue, and academic engagement between men and women. Yet, at this current research location, preliminary data shows the contrary. This study examined undergraduates’ perceived school support, self-esteem, academic fatigue, and engagement in two public Nigerian universities. The cross-sectional quantitative research using the non-experimental design was employed in the study, implementing self-concordance and demands-resources theories. The population of the study was undergraduate students undertaking degree courses at two public universities in Southwest Nigeria, and participants were selected using purposive and simple random sampling techniques. An instrument tagged